2006
DOI: 10.1111/j.1365-3083.2006.01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Influenza Vaccine Formulation with a Detailed Analysis of the Cytokine Response

Abstract: Vaccination provides the most effective method of limiting the impact of influenza. Inactivated influenza vaccines are available in three formulations and more information needs to be generated on how antigen presented in different vaccine formulations influences the subsequent immune response. In the present study, we have investigated the effect of two different influenza vaccine formulations on the resulting antibody and cytokine responses and compared these responses with influenza infection. Mice were vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 43 publications
14
20
0
Order By: Relevance
“…3D). The delayed induction of IgG1 antibodies was similar to that observed in mice intramuscularly immunized with a single dose of 15 g of split influenza vaccine (11,30). The addition of either mLT(R192G) or CTB significantly increased the levels of IgG2a by fourfold ( Fig.…”
Section: Dynamic Changes In the Ratios Of Igg1 And Igg2a Isotypes Tysupporting
confidence: 54%
See 1 more Smart Citation
“…3D). The delayed induction of IgG1 antibodies was similar to that observed in mice intramuscularly immunized with a single dose of 15 g of split influenza vaccine (11,30). The addition of either mLT(R192G) or CTB significantly increased the levels of IgG2a by fourfold ( Fig.…”
Section: Dynamic Changes In the Ratios Of Igg1 And Igg2a Isotypes Tysupporting
confidence: 54%
“…Studies of influenza VLPs as a vaccine candidate are still in an early developmental stage, and there is no detailed study of the kinetics of inducing virus-specific immune responses and protective efficacy after intranasal immunization with a single dose or two doses of influenza VLPs. Although limited previous studies demonstrated immune responses after one or two systemic vaccinations with inactivated whole virus or split vaccines (11,12,30), the HA dose-sparing effects on the kinetics of immune responses including isotypes of antibodies, functional antibodies, and protective efficacy, including lung viral titers and inflammation after lethal infection, remain largely unknown after mucosal vaccination. VLPs containing influenza M1 alone did not induce protective immune responses (25).…”
mentioning
confidence: 99%
“…This result is pertinent to the recent emphasis on the prognostic relevance of leukocytosis in both PV and ET. 7 Our findings also underline the potential confounding effect of sample accrual time on result interpretation. Finally, we underscore the fact that the current study utilized DNA from archived bone marrow and should not be compared with other studies that have used either DNA 2 Several studies have shown that selected aspects of a history of infection and vaccination may be related to the risk of LN.…”
mentioning
confidence: 66%
“…Depending on the formulation, whole or split inactivated influenza vaccine produces an immune response towards Th1 type of cytokines (IL-2 and IFN-g) or Th2 type of cytokines (IL-4, IL-10) respectively. 7 Repeated vaccinations could imbalance in the regulation and expression of Th1 and Th2 cytokines towards a Th1 thought to be protective against cancer. A shift in the balance of the Th1/Th2 response may play a role in aetiology of LNs as suggested by Holly et al 8 This hypothesis is also supported by recent findings that genetic variation in two key genes of Th2 pathway (IL-10, IL-4) could be associated with NHL.…”
mentioning
confidence: 99%
“…Whereas whole-virion vaccines are more immunogenic than other formulations (e.g., split and subunit vaccines) in humans and mice (7,(75)(76)(77)(78), they have been replaced by splitvirion types because of the high incidence of adverse effects such as febrile illness and local reactions at the injection site (79)(80)(81)(82). It is generally accepted that inflammatory cytokines produced from innate immune cells (i.e., DCs) are the primary cause of adverse effects in subjects vaccinated with whole-virion vaccines (75,83). Therefore, it is conceivable that a vaccine strategy selectively targeting B cell-intrinsic TLR signaling at the memory stage could reduce adverse effects while keeping the capacity for prompt recall response fairly intact.…”
Section: Discussionmentioning
confidence: 99%